Serbian: Serbian - Marković-Bajalović, Dijana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
The transfer of a property unit has been neglected in Serbian legal theory, although it has practical importance, especially in commercial relations. Companies and individual traders often sell or transfer in some other way a part of their property, which represents a functional or organisational unit. In Serbian law, the transfer of a property unit is regulated by Article 452 of the Law on Obligations - LO within the legal institute of joining a debt. In courts’ practice, the named legal provision often served as a basis to declare a transferee liable for the transferor’s debts. Applying Article 452 LO created problems because the law did not define the notion of the property unit and the conditions under which the transferee shall be liable for the transferor’s debts. The courts widely interpreted the concept of the property unit, extending the scope of application of Article 452 LO. The issue is additionally complicated, considering that Serbian scholars do not agree with the notion of property. This dispute reflects upon legislative solutions and courts’ practice. The author aims to reveal the legislator's original intent concerning the meaning and scope of Article 452 LO by analysing national legislation, courts’ practice and comparative law and providing historical interpretation. The ultimate goal is to point a direction in which courts should go when applying Article 452 and to give the legislator a proposal for its amendment.
Keywords: Serbian